2010
DOI: 10.1016/j.engstruct.2009.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Designing tensegrity modules for pedestrian bridges

Abstract: Tensegrity systems are spatial structures composed of tensile and compression components in a selfequilibrated state of prestress. The tensegrity concept has already been studied by researchers in various fields over the past decades. A family of tensegrity modules that can offer promising solutions for civil engineering applications such as tensegrity domes, towers and bridges is analyzed. Research into tensegrity systems has resulted in reliable techniques for form finding and structural analysis. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 22 publications
(26 reference statements)
2
52
0
Order By: Relevance
“…Moreover, the study of the kinematic and static properties of pre-stressed ring modules revealed that the pentagon module has no infinitesimal mechanisms and six independent states of self-stress. Furthermore, the pentagonal ring module was found to be structurally the most efficient module for the tensegrity footbridge application based on a structural efficiency index (Rhode-Barbarigos et al 2010a). Therefore, the pentagonal ring module was chosen as the elementary module for the deployable tensegrity bridge.…”
Section: Tensegrity-ring Modules and Footbridge Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study of the kinematic and static properties of pre-stressed ring modules revealed that the pentagon module has no infinitesimal mechanisms and six independent states of self-stress. Furthermore, the pentagonal ring module was found to be structurally the most efficient module for the tensegrity footbridge application based on a structural efficiency index (Rhode-Barbarigos et al 2010a). Therefore, the pentagonal ring module was chosen as the elementary module for the deployable tensegrity bridge.…”
Section: Tensegrity-ring Modules and Footbridge Applicationmentioning
confidence: 99%
“…Although tensegrity rings are composed of a single strut circuit, their deployment can be completed without strut collision. The "hollow rope" concept shows promise for architecture and civil engineering applications such as pedestrian bridges (Rhode-Barbarigos et al 2010b;Rhode-Barbarigos et al 2010a). However, its application for a deployable footbridge has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The bridge is composed of four ring-shaped tensegrity modules spanning 16m [25]. Symmetry about midspan is obtained by mirroring two modules.…”
Section: Design Characteristics Of the Tensegrity Bridgementioning
confidence: 99%
“…Design optimization of the tensegrity bridge was performed using member dimensions and selfstress level as design variables [43]. Struts were separated into two design groups: diagonal and intermediate struts.…”
Section: Tensegrity Bridgementioning
confidence: 99%
“…A side view of the tensegrity bridge is given in Figure 1. The bridge was composed of four ringshaped tensegrity modules spanning 20m [16,43]. Symmetry about midspan was obtained by mirroring two modules.…”
Section: Tensegrity Bridgementioning
confidence: 99%